Liberia's Infrastructure : A Continental Perspective - Foster, Vivien; Pushak, Nataliya (World Bank, Washington, DC, 2017)
Liberia's 14-year civil war left much of the country's infrastructure shambles. The country's 170 megawatt power generation capacity and national grid were completely destroyed. In Monrovia, just 0.1 percent of households had access to electricity. According to the 2008 National Census, access to piped water fell from 15 percent of the population in 1986 to less than 3 percent in 2008. The national road network was left in severe disrepair. Peace brought many positive developments. The Freeport of Monrovia is now privately managed and has resumed normal operations. Essential rehabilitation work has been carried out, and the port's performance now matches that of neighboring ports along the West African coast. Liberia has also successfully liberalized its mobile telephone markets, with access surging to 40 percent in 2009, at some of the lowest prices in Africa. Despite the potential for private investment, Liberia will likely need more than a decade to reach the illustrative infrastructure targets outlined in this report. Under business-as-usual assumptions for spending and efficiency, it would take at least 40 years for Liberia to reach these goals. Yet with a combination of increased finance, improved efficiency, and cost-reducing innovations, it should be possible to significantly reduce that time.